Pendampingan UMKM dalam Peningkatan Kualitas Pemasaran Berbasis Digital di Desa Bakung Lor Kecamatan Jamblang Kabupaten Cirebon - Layaman Layaman; Kintan Yuniar Rahmawati (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
MSME ASSISTANCE IN IMPROVING THE QUALITY OF DIGITAL-BASED MARKETING IN BAKUNG LOR VILLAGE, JAMBLANG DISTRICT, CIREBON REGENCY. Bakung Lor is a village located in Jamblang District, Cirebon, Regency, West Java, Indonesia. One of the icon Bakung Lor Village is Tape Ketan Bakung, this community service program is carried out in the Bakung Lor District of Jamblang Cirebon Regency. The partner from the activity program is the owner of UMKM Tape Ketan Lady Munil. In accordance with the problems that the partner faces, the efforts that can be made are improving business management through the marketing aspect of social media, production aspects, and the legality of business and products. The special target of community service activities is 1) improvement in business management through improving marketing quality on social media. 2) and the ownership of the legality of business and products that must always be used. The method used in community service activities is socialization and assistance. The solution provided to the marketing aspect is the expansion of market reach offline in stores and ambient convenience stores, and the use of online marketing information technology through trendy social media. In addition, the use of brand in the form of stickers/labels also help expand market share.